KAJIAN ETIKA BISNIS DAN LINGKUNGAN DI INDUSTRI ROKOK STUDI KASUS PT. HM SAMPOERNA - Joko Tri Haryanto (Jurnal Manajemen FE-UB, 2015)
Competition increasingly complex business, has made the company just run with the mission of pursuing material wealth and commercial advantage. Economic approach then make companies more aggressive in competing expand its business networl. The companies are then likely to make a profit as much as possible, without thinking about the social and environmental concers to which it asppires. Along with the development of public awareness and environmentas movements, the company was still able to benefit greatly with regard to business ethics and the environment in the from Corporate Social Responsibilities (CSR). By using descriptive statistical approach to the PT. HM Sampoerna, it can be concluded thet the companies engaged in industries that counter business ethics and the environment, still can provide benefits to the community, the nation and the environment when carrying out CSR programs as a whole and consistent. Keywords : Ethics, CSR, Business and Environmant Ethics